A case of tracheal obstruction caused by reflux and aspiration of semi-solid nutrients via the nasogastric tube. (2019) - Nakagawa, Masatoshi; Sugihara, Kaori; Isobe, Kiyoshi; Akasu, Masafumi; Tsujimoto, Kazutaka; Itsui, Yasuhiro; Nakajima, Yasuaki
Highlights: There are not sufficient data on viscosity of semi-solid nutrients via the nasogastric tube in vivo. Tracheal obstruction occurred by reflux and aspiration of semi-solid nutrients through the nasogastric tube Reflux of semi-solid nutrients is rare, but once it occurs, it can be fatal. Abstract: Introduction: Semi-solid nutrients have several advantages, including reduced cases of diarrhea and aspiration pneumonia, and are usually administered via percutaneous endoscopic gastrostomy owing to its high viscosity. Administering semi-solid nutrients via a nasogastric tube was recently introduced in clinical practice; however, its safety has not been well confirmed. Presentation of case: An 82-year-old man with a right occipital hemorrhage and severe diarrhea consulted the nutritional support team. Administrations of semi-solid nutrients (HINE E-GEL®) via the nasogastric tube was initiated, which gradually alleviated his symptoms. Fourteen days after initiation, he suddenly had pulmonary failure owing to a tracheal obstruction caused by the reflux and aspiration of semi-solid nutrients. Intubation and subsequent reflex cough expectorated sputum with gel-form particles, which quickly stabilized his pulmonary condition. After this, his hospital course was stable, and he was referred to another hospital for further rehabilitation. Discussion: Semi-solid nutrients administered via the nasogastric tube have different ingredients compared with those administered via percutaneous endoscopic gastrostomy. HINE E-GEL®, for example, contains pectin and calcium phosphate that changes from liquid to semi-solid inside the stomach via chemical reactions under acidic conditions. Data on the viscosity of HINE E-GEL® in vivo are insufficient. Uncertainty regarding the form and viscosity of HINE E-GEL® inside the stomach complicates clinical practice. Conclusions: Although semi-solid nutrients have several advantages, including reduced diarrhea and gastroesophageal reflux, evidence on semi-solid nutrients via the nasogastric tube is insufficient. It should be noted that semi-solid nutrient reflux can be more fatal than liquid nutrients.